Provenance, age constraints and metamorphism of Ediacaran metasedimentary rocks from the El Triunfo Complex (SE Chiapas, México): evidence for Rodinia breakup and Iapetus active margin. Issue 16 (9th December 2016) - González-Guzmán, Reneé; Weber, Bodo; Manjarrez-Juárez, Román; Cisneros de León, Alejandro; Hecht, Lutz; Herguera-García, Juan Carlos
ABSTRACT: Metasedimentary rocks from the El Triunfo Complex (Jocote Unit) in the southern Chiapas Massif (SE México) are constituted mainly by sillimanite-rich micaschist, locally intercalated with marble and calc-silicate rocks. Mafic rocks (now amphibolite) intruded the sequence prior to deformation and folding. Peak metamorphic conditions are estimated by geothermobaromerty at 6.0 kbar and 650ºC. The timing of the metamorphic event is dated by LA-MC-ICPMS analysis on zircon rims at 438 +23 /–12 Ma. Furthermore, detrital zircon grains yield mainly Stenian–Tonian and minor early Mesoproterozoic ages, indicating provenance from Grenville-type orogens (such as Oaxaquia) and some older cratonic sources. The 87 Sr/ 86 Sr values of 0.70775–0.70777 and the δ 13 C values from +1.9‰ to +2.7‰ in associated calcite marble define the time of deposition between 600 and 580 Ma. Geochemical markers from metapelite samples (such as La/Th > 3.94, La/Sc > 3.72, Th/U > 8.19, Th/Co > 0.42 and CIA = 74 to 83), as well as Sm–Nd isotope data ( ε Nd i = −8.1 to −4.0, TDM(Nd) = 1.65–1.32 Ga) suggest weathering of Mesoproterozoic felsic rocks during temperate to warm climate. Furthermore, Zr/Sc values (9.1–21.0), chondrite-normalized REE patterns [La/Yb] N = 10.3–23.3, Eu/Eu* < 0.64), and ΔHf values (1.98–10.02) are indicative of pelagic and zircon-depleted sediments of a passive margin. The results suggest that the Jocote Unit was deposited during the opening of the Eastern Iapetus Ocean in the Ediacaran Period. This is the first evidence for Rodinia breakup in southern México. Besides that, the Ordovician tectonothermal event is probably related to compression during subduction and accretion along the western margin of Gondwana.